2021
DOI: 10.1021/acs.bioconjchem.1c00351
|View full text |Cite
|
Sign up to set email alerts
|

Non-Genetic Generation of Antibody Conjugates Based on Chemoenzymatic Tyrosine Click Chemistry

Abstract: The availability of tools to generate homogeneous and stable antibody conjugates without recombinant DNA technology is a valuable asset in fields spanning from in vitro diagnostics to in vivo imaging and therapeutics. We present here a general approach for the conjugation to human IgG1 antibodies, by employing a straightforward two-stage protocol based on antibody deglycosylation followed by tyrosinase-mediated orthoquinone strain-promoted click chemistry. The technology is validated by the efficient and clean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…[18] Therefore, less reactive constructs such as dibromophenylbenzoate and ANANS proved superior due to cleaner and more controllable modification (Figure 4a). [16] In fact, a study by Hamachi revealed that more stable constructs lead to POI modification that kinetically competes with rapid click reactions. [26] The positions of the linkers shown above are indicated by the red arrows, and the corresponding numbers on the linker length and effective concentration are given.…”
Section: The Poi Modifying Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] Therefore, less reactive constructs such as dibromophenylbenzoate and ANANS proved superior due to cleaner and more controllable modification (Figure 4a). [16] In fact, a study by Hamachi revealed that more stable constructs lead to POI modification that kinetically competes with rapid click reactions. [26] The positions of the linkers shown above are indicated by the red arrows, and the corresponding numbers on the linker length and effective concentration are given.…”
Section: The Poi Modifying Unitmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Alternatively, modification of isolated proteins has resulted in superior treatments, as is clear from the recent surge in the developments of antibody-drug conjugates (ADCs). [9] For both avenues, approaches have been developed to incorporate a unique chemically [10,11] and/or enzymatically [12][13][14][15][16] reactive moiety in the protein. [17] In this concept paper, modification strategies for wild-type proteins are surveyed and guiding principles for an integrated toolbox for the modification of a range of wildtype proteins are derived.…”
Section: Introductionmentioning
confidence: 99%
“…Following a similar strategy as with cysteine engineering, researchers described tyrosine engineering by combining the insertion of a tyrosine residue at a surface exposed position with conjugation of a tyrosine-reactive moiety for the generation of ADCs [84,85]. Proteinogenic amino acids can be introduced into antibodies by straight forward genetic mutations but do only offer limited orthogonality in their reactive groups.…”
Section: Linking Up: Advances In Site-directed Conjugation and Linker...mentioning
confidence: 99%
“…11 While the synthesis of ADCs using this bioconjugation strategy has previously been reported, this work represents the rst application of this technology to radiopharmaceutical chemistry andmore importantlythe rst in vivo evaluation of any immunoconjugate synthesized in this manner. [12][13][14] Indeed, we contend that this strategy represents a step forward compared to extant chemoenzymatic approaches to radiolabeling because it (a) is faster, (b) involves fewer steps, (c) relies on cheaper and easier-to-make reagents, and (d) employs more widely used and commonly available enzymes.…”
mentioning
confidence: 99%